Gestão de organizações sem fins lucrativos: uma avaliação de desempenho através do balanced scorecard - Lutif Junior, Jorge Assef (2012)
The methodology Balanced Scorecard (BSC) focuses on the major critical issues of modern organizations, whether with or without profit. The measurement of the effective performance of the latter is by evaluating the successful implementation of organizational strategy. The aim of this paper is to present the development of a system of performance measurement strategy for a nonprofit organization, whose object of study is the Associação de Apoio as Comunidades do Campo - AACC, in the context of the BSC methodology of Kaplan and Norton. The methodology of this case study is an exploratory, descriptive and qualitative, and diagnose the coherence of the Strategy Map in an organization, based strategic planning from 2010 to 2012. Initially conducted a literature review covering the main aspects of strategy maps and performance evaluation involving the translation of the BSC and strategy evaluation. The main results of the proposed approach refers to evaluation of overall scores for each dimension of the BSC methodology, financial, customer, internal processes, learning and growth. These results are able to help the organization evaluate and revise their strategy and, in general, to adopt management methods more accurately. Data collection is centered on interviews with semi-structured questionnaire. The findings highlight on balancing and alignment of strategic objectives, low causality map, strategic communication insufficient and fragmented. For interviewees organizational culture is the biggest impediment to structuring a management model based on indicators and strategic process should be initiated by non-financial indicators gradually. The performance indicators of the AACC/RN portray more meritocracy operational procedures of social projects in the context of the Strategic Map determined in a shortterm over the long term. However, there is evidence of improved performance management and strategic taken as a basis of planning as both the strategic map structured. Therefore, the nonprofits need to adopt a form of management that enables planning, setting objectives and targets that provide the continuity of its activities, and generating instruments that can measure the financial performance and non-financial, in order to develop strategic actions for growth and sustainability